Efficacy of Laser Vs Pneumatic Lithotripsy for Mid and Distal Ureteric Stone: A Comparative Study - Shah, Ram Sagar; Shrestha, Nischal (Journal of Nepalgunj Medical College, 2022)
Introduction: Urolithiasis refers to a condition characterized by the formation or occurrence of calculi in the urinary tract. In Asia, about 1%-19.1% of the population suffers from urolithiasis. Pneumatic and laser intra corporeal lithotripsy are mostly preferred and frequently used during endoscopic management for ureteral stone. Aims: This study was done to compare the efficacy of the laser versus pneumatic lithotripsy. Methods: This was a prospective comparative study conducted from May 2019 to April 2020 in Nobel Medical College and Teaching Hospital, Biratnagar. Patients with mid- or distal ureteric calculi of size 5mm and more or failed medical management were included in the study. The patients were equally divided into two groups: laser & pneumatic. The efficacy of the procedure was measured in terms of stone clearance. Stone size less than 5mm, nephrolithiasis on same side of ureteric stone, pregnancy, bleeding disorder and patient not giving consent were excluded from the study. Results: Total 130 patients were enrolled in this study. The stone clearance was observed in 86.15% in pneumatic group and 96.92% in laser group at the end of 6 weeks. In pneumatic group 13.85% did not achieve stone clearance where as in laser group it was 3.08%. In patients with mid ureteric stone the clearance rate was significantly higher in laser group (93.33%) than in pneumatic group.(p=0.041) When the clearance rate of two techniques were compared for distal ureteric stone the results were similar. The mean operation time was 28.89 ± 8.26 min in pneumatic group and 22.93 ± 6.05 min in laser group(p<0.05). Conclusion: Holmium: YAG laser lithotripsy is superior to pneumatic lithotripter in terms of stone clearance rate for the mid ureteric calculus and also less time consuming.